Efektivitas Model Pembelajaran Contextual Teaching and Learning Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Wulandari, Inayah; Hermawan, Hermawan (Indo-MathEdu Intellectuals Journal, 2024)
The problem in this study is the low mathematical problem-solving ability of students. This study aims to determine the effectiveness of the Contectual Teaching and Learning (CTL) learning model on students' mathematical problem-solving skills. The method in the study is a quasi-experiment with the chosen research design is Non-equivalent Pretest-Posttest Control Group Design. Samples were taken by purposive sampling consisting of class VIII C (Experimental Class) and class VIII A (Control Class). The number of students in both classes is the same, namely 16 students, the total sample is 32 students. Data collection was carried out through a problem-solving ability test. Data analysis was carried out using the t-test and N-Gain test. The results of the hypothesis test on the results of the posttest data were obtained from the conclusion that there was a difference in students' mathematical problem-solving abilities after applying the Contectual Teaching and Learning (CTL) model in the experimental class and the conventional model in the control class. There was a significant increase in students' mathematical problem-solving ability in the experimental group compared to the students' mathematical problem-solving ability in the control group. The students' response to the Contectual Teaching and Learning (CTL) learning model in the experimental class received a positive response with a very high interpretation of the questionnaire results, which was 77%.